Conversion from dose length product to effective dose for the CT component of whole-body PET/CT - Inoue, Yusuke; Ohkubo, Yu; Nagahara, Kazunori; Uehara, Ayuka; Takano, Makoto (Annals of Nuclear Medicine, 2022)
Objective For dose management of CT, the ratio of effective dose (ED) to dose length product (DLP) is often used to convert DLP to ED. We evaluated this ratio in the CT component of whole-body PET/CT performed under various imaging conditions to determine a practical method for ED estimation applicable to PET/CT. Methods In total, 400 patients who underwent whole-body PET/CT were enrolled. The imaging conditions were variable in terms of the scanner model, setting of automatic exposure control (AEC) setting and arm positioning. The scan range was divided into six anatomical regions. DLP was calculated for each region, and multiplied by the conversion factor for the respective region to determine regional ED. The six regional EDs were summed together to determine ED by the regional DLP method (ED rDLP ). Additionally, regional ED was assessed using CT-Expo, software dedicated to CT dose estimation, and the total of six regional EDs were defined as ED by the CT-Expo method (ED CT-Expo ). ED rDLP /DLP and ED CT-Expo /DLP were calculated using DLP automatically provided by the scanner. Results ED rDLP /DLP ranged from 0.0121 to 0.0128 mSv/mGy/cm with the arms up and from 0.0127 to 0.0134 mSv/mGy/cm with the arms down. Putting the arms down slightly increased ED rDLP /DLP, presumably due to an increased contribution of the chest and abdomen to total radiation exposure. The AEC setting and scanner model also influenced ED rDLP /DLP significantly but slightly. ED CT-Expo /DLP showed apparent scanner dependence, which appeared mainly attributable to differences in the constants used for DLP calculation between the scanner and CT-Expo. Conclusion Multiplication of scanner-derived DLP by a conversion factor of 0.013 mSv/mGy/cm provides acceptable ED estimates.